THE IMPACT OF FORMATIVE ASSESSMENT ON ENGLISH LANGUAGE LEARNERS’ MOTIVATION - Xomidjonova Gavharoy Xayrullo qizi, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract: Formative assessment plays a crucial role in the language learning process by providing continuous feedback and encouraging student reflection. This article explores how formative assessment strategies affect the motivation of English language learners (ELLs) in classroom settings. Based on teacher interviews, classroom observations, and literature analysis, the study finds that formative assessments—such as peer reviews, self-assessment, progress tracking, and feedback loops—positively influence learners’ engagement, self-confidence, and goal-setting behavior. While challenges exist, particularly in standardization and teacher preparedness, the findings suggest that well-structured formative assessment significantly enhances learner motivation and language acquisition.